2012
DOI: 10.1039/c2cp40754j
|View full text |Cite
|
Sign up to set email alerts
|

Charge localization increases chemical expansion in cerium-based oxides

Abstract: In this work, we demonstrate the mechanism by which electronic charge localization increases the chemical expansion coefficient in two model systems, CeO 2Àd and BaCeO 3Àd . Using Density Functional Theory calculations, we predict that this coefficient is increased by more than 70% when charge is fully localized, consistent with the observation that materials with a smaller degree of charge localization have smaller chemical expansion coefficients. This finding has important consequences for devising materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 42 publications
6
84
1
Order By: Relevance
“…The importance of charge localization was also recognized in a subsequent study. 17 An interesting result of our investigation was that the contraction due to the formation of an oxygen vacancy in ZrO 2 (upon acceptor doping) is 91% larger than in CeO 2 , leading to our prediction that a CeO 2 -ZrO 2 solid solution will have a smaller chemical expansion coefficient. 16 In this communication, we test this hypothesis, both experimentally and computationally, and show that the solid solution indeed exhibits a signicant ($50%) decrease in a C .…”
Section: Broader Contextmentioning
confidence: 76%
“…The importance of charge localization was also recognized in a subsequent study. 17 An interesting result of our investigation was that the contraction due to the formation of an oxygen vacancy in ZrO 2 (upon acceptor doping) is 91% larger than in CeO 2 , leading to our prediction that a CeO 2 -ZrO 2 solid solution will have a smaller chemical expansion coefficient. 16 In this communication, we test this hypothesis, both experimentally and computationally, and show that the solid solution indeed exhibits a signicant ($50%) decrease in a C .…”
Section: Broader Contextmentioning
confidence: 76%
“…This phenomenon, known as chemical expansion, is most pronounced for perovskites containing transition metal ions that can adopt a variety of valence states and hence can readily accommodate the associated change in formal charge 9 . Prominent examples are acceptor doped LaMnO 3 and donor doped SrTiO 3 10,11 , where significant volume expansions are observed as a function of the oxygen partial pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Marrocchelli et al suggested that zero chemical expansion in a material could be obtained by choosing material compositions that balance these two effects. In later, related work, Marrocchelli et al determined that charge localization at the cation increased chemical expansion relative to a structure with distributed charge [92]. With localized charge, the change in the radius of ceria upon reduction would be greater than if the charge were delocalized, causing an increase in chemical expansion for structures with higher degrees of charge localization.…”
Section: Chemical Expansion In Ionically Conductive Ceramicsmentioning
confidence: 99%
“…Marrocchelli et al used DFT + U (indicating inclusion of a Hubbard term) to calculate the effect of charge delocalization on the chemical expansion coefficient of CeO 2−δ and BaCeO 3−δ [92]. In that study, varying the U term changed the extent of localization of 4f electrons at the ceria cation.…”
Section: Atomistic Modelingmentioning
confidence: 99%
See 1 more Smart Citation